WHAT BOTHERS THE BABY? - E.S. Sakharova (Педиатрическая фармакология)
The article discusses the causes of restless behavior in infants: Issues of diagnostics for functional disorders of gastrointestinal tract, sleep physiology and pathology in infants, as well as ways to correct these conditions.Key words: infants, protosomnia, intestinal colics. (Pediatric Pharmacology. – 2010; 7(2):143-148)